2021
DOI: 10.3892/or.2021.8187
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally elevated ubiquilin‑1 expression in breast cancer regulates metastasis and stemness via AKT signaling

Abstract: Ubiquilin-1 (UBQLN1) is an essential factor for the maintenance of proteostasis in cells. It is important for the regulation of different protein degradation mechanisms, including the ubiquitin-proteasome system, autophagy and endoplasmic reticulum-associated protein degradation pathways. However, the role of UBQLN1 in cancer progression remains largely unknown. In the present study, the expression, functions and molecular mechanisms of UBQLN1 in breast cancer tissue samples and cell lines were explored. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…For instance, some studies have reported that TBL1XR1 promotes CSCs properties and metastasis in gastric cancer [ 44 ]. In addition, the inhibition of UBQLN1 reduced the invasion and cancer stemness of breast cancer [ 45 ]. Moreover, the inhibition of Dicer expression enhanced the CSCs properties and metastasis in colon cancer cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies have reported that TBL1XR1 promotes CSCs properties and metastasis in gastric cancer [ 44 ]. In addition, the inhibition of UBQLN1 reduced the invasion and cancer stemness of breast cancer [ 45 ]. Moreover, the inhibition of Dicer expression enhanced the CSCs properties and metastasis in colon cancer cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies demonstrated that UBQLN1 was involved in crucial biological processes of several cancers [14,[28][29][30][31][32][33], especially epithelial-to-mesenchymal transition (EMT). EMT is a process in which epithelial cells acquire mesenchymal features.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is of importance to understand the relationship between UBQLN1 and EMT pathways in different kinds of cancers. Feng et al discovered that UBQLN1 silencing can inhibit EMT and MMP expression via AKT signaling in breast cancer [33]. Shah et al found that UBQLN1 played an important part in EMT of human non-small cell lung cancer cells and repressed migration [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UBQLN1 is related to the occurrence and progression of a variety of human tumors. UBQLN1 is abnormally upregulated in breast cancer, and the knockdown of UBQLN1 inhibited the invasion and stemness of breast cancer cells through the AKT pathway [ 13 ]. In non-small cell lung carcinoma, loss of UBQLN1 repressed EMT [ 14 ].…”
Section: Introductionmentioning
confidence: 99%